Problem of students of elementary school teacher program in creating ethnomathematic-based lesson plan of Kraton Yogyakarta: A case study - Luluk Mauluah; Eka Cahya Sari Putra (Universitas negeri Yogyakarta, 2021)
The lesson plan serves as an essential learning guide in the learning implementation. To improve the learning quality, lesson plans are generally developed based on some particular learning models, strategies, media, materials, and philosophies. Ethnomathematics is a recently developed learning model, and thus the development of ethnomathematics-based lesson plans to introduce and encourage cultural awareness is still not widely practiced. This research aims to reveal students' problems and difficulties in preparing ethnomathematics-based lesson plans, and the characteristics of lesson plans related to ethnomathematics. The experience of 10 students of the Elementary School Teacher Education (PGSD) program at Universitas Negeri Yogyakarta (UNY) about the difficulties in creating an ethnomathematics-based lesson plan is used as a case study. The in-depth interviews revealed the following difficulties of these students in preparing a lesson plan: syntax, methods, and models, with the extent to which ethnomathematics should be presented in the lesson plan being the most essential problem.